Magnetic Resonance Lymphography at 9.4 T Using a Gadolinium-Based Nanoparticle in Rats: Investigations in Healthy Animals and in a Hindlimb Lymphedema Model. Issue 12 (December 2017) - Müller, Andreas; Fries, Peter; Jelvani, Bijan; Lux, François; Rübe, Claudia E.; Kremp, Stephanie; Giovanoli, Pietro; Buecker, Arno; Menger, Michael D.; Laschke, Matthias W.; Frueh, Florian S.
Abstract : Objectives: Magnetic resonance lymphography (MRL) in small animals is a promising but challenging tool in preclinical lymphatic research. In this study, we compared the gadolinium (Gd)-based nanoparticle AGuIX with Gd-DOTA for interstitial MRL in healthy rats and in a chronic rat hindlimb lymphedema model. Materials and Methods: A comparative study with AGuIX and Gd-DOTA for interstitial MRL was performed in healthy Lewis rats (n = 6). For this purpose, 75 μL of 3 mM AGuIX (containing 30 mM Gd-DOTA side residues) and 75 μL 30 mM Gd-DOTA were injected simultaneously in the right and left hindlimbs. Repetitive high-resolution, 3-dimensional time-of-flight gradient recalled echo MRL sequences were acquired over a period of 90 minutes using a 9.4 T animal scanner. Gadofosveset-enhanced MR angiography and surgical dissection after methylene blue injection served as supportive imaging techniques. In a subsequent proof-of-principle study, AGuIX-based MRL was investigated in a hindlimb model of chronic lymphedema (n = 4). Lymphedema of the right hindlimbs was induced by means of popliteal and inguinal lymphadenectomy and irradiation with 20 Gy. The nonoperated left hindlimbs served as intraindividual controls. Six, 10, and 14 weeks after lymphadenectomy, MRL investigations were performed to objectify lymphatic reorganization. Finally, skin samples of the lymphedematous and the contralateral control hindlimbs were analyzed by means of histology and immunohistochemistry. Results: AGuIX-based MRL resulted in high-resolution anatomical depiction of the rodent hindlimb lymphatic system. Signal-to-noise ratio and contrast-to-noise ratio of the popliteal lymph node were increased directly after injection and remained significantly elevated for up to 90 minutes after application. AGuIX provided significantly higher and prolonged signal intensity enhancement as compared with Gd-DOTA. Furthermore, AGuIX-based MRL demonstrated lymphatic regeneration in the histopathologically verified chronic lymphedema model. Collateral lymphatic vessels were detectable 6 weeks after lymphadenectomy. Conclusions: This study demonstrates that AGuIX is a suitable contrast agent for preclinical interstitial MRL in rodents. AGuIX yields anatomical imaging of lymphatic vessels with diameters greater than 200 μm. Moreover, it resides in the lymphatic system for a prolonged time. AGuIX may therefore facilitate high-resolution MRL-based analyses of the lymphatic system in rodents.